Improvement plan to reduce the operating costs of the company Tableros La Perla del Huallaga S.A.C. applying engineering tools (LACCEI, 2024)
The present work was carried out in the company Tableros Perlas del Huallaga S.A.C, whose main activities are the processing and sale of melamine and wooden planks. To begin with, a diagnosis of the problematic situation of the company was made, in which it was identified that there were various problems such as: processes stopped due to lack of raw material, lost sales due to not being able to meet the demand, idle time for operators and production stops. failure machines Therefore, a calculation was made of the costs that these problems generated for the company, managing to cause economic losses in the last six months. Therefore, an improvement plan was prepared to determine the monetary costs incurred by the aforementioned problems and reduce them by approximately 25%. For this reason, industrial engineering tools were used, such as: 5s Methodology, Line Balance, TPM (Total Productive Maintenance) and JIT (Just In Time). The implementation of the plan was simulated through the ProModel version 2016 software and the Montecarlo simulation model. It was obtained as results that the improvement plan reduces costs to S/. 97,187.67, which represents a reduction of 27% which verifies the hypothesis. Finally, the economic evaluation of the improvement plan was carried out, where an IRR of 179% was obtained, a NPV of S/. 332,027.66 and a B/C of S/. 2.17, whose indicators demonstrate the feasibility and profitability of applying the improvement plan in the company. So that the company can increase its profits for the next periods.